Official certified ethical hacker review guide, version 7.1 - DeFino, Steven (Course Technology, 2013)
OFFICIAL CERTIFIED ETHICAL HACKER REVIEW GUIDE: FOR VERSION 7.1 is a valuable resource to help you pursue the most recognized, respected hacking certification in the world. As experienced instructors of the International Council of Electronic Commerce Consultants (EC-Council), the authors draw on firsthand experience training top-caliber information security professionals for success on the council's Certified Ethical Hacker (CEH) exam. The only exam review guide officially endorsed by the EC-Council, this proven resource focuses on the core concepts that are covered on the newest certification course (version 7.1), as well as a wide array of useful learning tools, including chapter objectives, step-by-step tutorials, "Try it Out" exercises and challenges, , group discussion topics, short lab examples, and practice exam questions and answers with explanations.The official CEH course teaches the latest hacking techniques, exploits, automated programs, and defensive recommendations, preparing students to audit organizations' protection of their information assets through a deep understanding of the methodologies and tools of the attack process. This official CEH Exam review guide can be used to either preview and prepare for this comprehensive course or review afterwards to prepare for the challenging exam. It is the perfect complement that gives any student a real advantage toward success with this certification.